Editorial - Capogna, Stefania (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Challenges and opportunities for education, training and work systems in the emergency period: this is the title of this issue dedicated to recounting the attempts and strategies to recover from the devastating effects, on a social and economic level, caused by the global pandemic. The fil rouge that unites all the contributions in the columns and essays can be summarised in the creative, reflective and generative drive that the individual is able to activate, drawing on his or her personal and community resources, to cope with crisis situations. The key words through which it is possible to outline the state of mind that has dominated the collective space in the last two years are uncertainty, bewilderment, fear in the face of the crumbling of traditional safety nets, resulting in an increase in inequalities and poverty, and a strong sense of loneliness. It is in coping with this state of extreme and unimaginable discomfort in the comfort zone of modern society, which foresees and controls everything, that people, alone and/or together, have been able to put their best resources to the test, discovering resilience, releasing positive emotions, investing in the common good as an alternative, activating new forms of cooperation, in order to tackle complex problems and common difficulties.